Comparisons of the volumetric efficiency and combustion characteristics between CNG-DI and CNG-PFI engines. (5th July 2017) - Song, Jingeun; Choi, Minhu; Park, Sungwook
Highlights: Volumetric efficiencies of DI and PFI were similar for early injection conditions. 1D simulation code (AMESim) was used to investigate the intake process in detail. For various injection timings, the volumetric efficiency of PFI was kept constant. Late fuel DI increased volumetric efficiency and fuel conversion efficiency. DI after IVC was the best injection strategy for high engine power and efficiency. Abstract: In the present study, the volumetric efficiency and combustion characteristics of compressed natural gas (CNG) direct injection (DI) and port fuel injection (PFI) were compared. In a single-cylinder engine, various fuel injection timings were tested for each fuel injection position, and the volumetric efficiency of each test condition was calculated from the intake flow rate. The one-dimensional simulation program AMESim was also used to further investigate the intake process. Experimental and numerical results showed that the volumetric efficiency was not influenced by the position of the injector. For the early fuel injection, before the intake valve close (IVC), the volumetric efficiencies of the DI and PFI were similar to each other; the averaged volumetric efficiencies were both about 38.62% and the standard deviations of volumetric efficiency were less than 0.2%. However, as the fuel injection timing was retarded after the IVC, the volumetric efficiency of DI increased while the volumetric efficiency of PFI was kept constant or slightly decreased. The increase in the volumetric efficiency was due to the fact that the fuel volume did not occupy the cylinder volume during the intake stroke. Combustion was stable for all the test conditions. The coefficient of variation of the indicated mean effective pressure (COVIMEP ) was lower than 1.5%. The highest fuel conversion efficiency was observed for late fuel direct injection, after the IVC, due to the fastest combustion. Thus, by applying the late fuel injection timing after IVC, the CNG-DI could have a higher volumetric efficiency and fuel conversion efficiency than the CNG-PFI.